2019
DOI: 10.1038/s41598-018-37193-3
|View full text |Cite
|
Sign up to set email alerts
|

Human pluripotent stem cell-derived alveolar epithelial cells are alternatives for in vitro pulmotoxicity assessment

Abstract: Human pluripotent stem cell (hPSC)-derived alveolar epithelial cells (AECs) provide new opportunities for understanding lung development and the treatment of pulmonary diseases. However, toxicity assessments using hPSC-AECs have not been undertaken. In this study, we generated functional AECs from hPSCs and evaluated their inflammatory and apoptotic responses to cadmium (Cd) exposure (1, 5, and 10 μM) for 24 h compared with the human bronchial epithelial cell line (BEAS-2B) and primary AECs as controls. Our da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…Our system is based on optimized stepwise direct hPSC differentiation via mimicking of early alveolar developmental cues in a temporally controlled manner [ 25 ]. Furthermore, we have previously demonstrated that hPSC-derived AECs displayed similar phenotypes and cellular responses to cadmium exposure as those of hpAECs [ 26 ]. Using our efficient and reproducible protocols, we found that dPM2.5 exposure perturbed AEC differentiation and resulted in loss of epithelial features of hPSC-derived AECs and AOs, which was evidenced by upregulation of mesenchymal-related genes and EMT-mediated nuclear TFs.…”
Section: Discussionmentioning
confidence: 99%
“…Our system is based on optimized stepwise direct hPSC differentiation via mimicking of early alveolar developmental cues in a temporally controlled manner [ 25 ]. Furthermore, we have previously demonstrated that hPSC-derived AECs displayed similar phenotypes and cellular responses to cadmium exposure as those of hpAECs [ 26 ]. Using our efficient and reproducible protocols, we found that dPM2.5 exposure perturbed AEC differentiation and resulted in loss of epithelial features of hPSC-derived AECs and AOs, which was evidenced by upregulation of mesenchymal-related genes and EMT-mediated nuclear TFs.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory as well as others have successfully differentiated iPSCs to distal lung phenotypes that mimic type I and type II alveolar cells ( Mitchell et al, 2017 ; Wang et al, 2020 ; Alysandratos et al, 2020 preprint). Type I and type II alveolar cells are implicated in the functional regeneration of the distal lung after damage and are an excellent source for modeling hyperoxia-induced BPD ( Jacob et al, 2017 ; Heo et al, 2019 ). In addition to studying cell development using cell culture, explant lung culture is another option to investigate specific pathways and novel interactions affected by hyperoxic conditions.…”
Section: In Vitro Modelsmentioning
confidence: 99%
“…Consequently, they showed that clinical viruses acquire genome-wide changes, leading to alterations in the viral surface glycoproteins, which is conductive for viral entry ( 15 ). Heo et al ( 16 ) have shown that hPSC-derived alveolar epithelial cells alleviated apoptotic and inflammatory responses against cadmium exposure. Recently, the established hPSC-derived epithelial cells are generated with alveolar epithelial organoids (AOs), and AOs treated with TGF-β1 exhibited collagen accumulation and fibrotic changes in the interstitial area of AOs ( Fig.…”
Section: Current Experimental Ipf Modelingmentioning
confidence: 99%